2021
DOI: 10.1096/fj.202100787r
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extracellular vesicles tau and β‐amyloid as biomarkers of cognitive dysfunction of Parkinson's disease

Abstract: The contribution of circulatory tau and β‐amyloid in Parkinson's disease (PD), especially the cognitive function, remains inconclusive. Extracellular vesicles (EVs) cargo these proteins throughout the bloodstream after they are directly secreted from many cells, including neurons. The present study aims to investigate the role of the plasma EV‐borne tau and β‐amyloid as biomarkers for cognitive dysfunction in PD by investigating subjects with mild to moderate stage of PD (n = 116) and non‐PD controls (n = 46).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…EVs in this study were isolated using the exoEasy Maxi kit, and confirmed to be mainly exosomes by the presence of exosomal markers CD9, CD63 and TSG 101. The levels of tau and Aβ1-42 in the EVs were measured by immunomagnetic reduction assay [ 84 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…EVs in this study were isolated using the exoEasy Maxi kit, and confirmed to be mainly exosomes by the presence of exosomal markers CD9, CD63 and TSG 101. The levels of tau and Aβ1-42 in the EVs were measured by immunomagnetic reduction assay [ 84 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Aβ and tau have also been detected in exosomes/extracellular vesicles (EV). Although tau and Aß42 plasma EV levels did not differ between PD patients and controls, elevated levels of both proteins were significantly associated with cognitive impairment and combined with other parameters including aSyn in EV identified cognitively impaired PD patients with high accuracy (Chung et al 2021 ).…”
Section: Blood-based Biomarkermentioning
confidence: 99%
“…EVs and particularly exosomes have a large potential as non-invasive diagnostic biomarker carriers for neurodegenerative diseases and various studies reported them as being a source for biomarkers in Alzheimer’s disease (AD) [ 58 , 59 , 60 , 61 , 62 ], Parkinson’s disease (PD) [ 63 , 64 , 65 , 66 , 67 ], amyotrophic lateral sclerosis (ALS) [ 50 , 68 , 69 ], and prion disease [ 48 ]. The amyloid β (Aβ), tau, α-synuclein, and superoxide dismutase 1 were previously quantified in EVs in AD, PD, and ALS, and in several studies the correlation of their levels with the disease stages were found [ 51 , 60 , 64 , 70 , 71 , 72 , 73 , 74 ]. In HD, information about protein composition of EVs is missing [ 57 ] and the presence of HTT protein or its fragments in the EVs isolated from blood plasma have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%